Tunica albuginea cyst presenting with milk of calcium - Erdal Karavas (Urology Annals, 2019)
Tunica albuginea cysts are rarely seen but are important and can be diagnosed easily with ultrasonography. Calcium milk is defined as the precipitation of calcium in a cyst or other fluid-containing structure and can be seen in many organs. In this case report, calcium milk seen in a tunica albuginea cyst is discussed.